How Multidimensional Proximity Affects Collaborative Innovation Performance in New Energy Vehicles - Zhang, Yarui; Li, Xiaocui; Lu, Junsheng; Mao, Xueli (Transformations In Business & Economics, 2025)
The collaborative innovation performance in new energy vehicles (NEVs) is significantly affected by such factors as geographical proximity, technological proximity, and organizational proximity among innovation subjects, but the dynamic influence of multidimensional proximity on collaborative innovation performance has been scarcely investigated. To identify the influence of proximal cooperative relationships on the innovation performance in NEVs, this study employed the cooperative patent data of NEVs in China from 2005 to 2022 and applied the social network analysis method and quadratic assignment procedure （QAP）analysis method to verify the influence of multidimensional proximity on collaborative innovation in NEVs in different periods on the basis of transaction cost theory and resource dependence theory. Results show that proximity is an important influencing factor of cooperative relationships, and proximity factors affect cooperation differently in diverse development periods of the NEV industry. Specifically, technological proximity plays a significant positive role in promoting collaborative innovation, while geographical proximity and organizational proximity have a reduced effect on collaborative innovation. The obtained conclusions reveal the influence mechanism of multidimensional proximity on the collaborative innovation in NEVs to some extent, which can provide decision-making references for the deep integration of NEV industry–university–research.